Insuficiência Pancreática Exócrina. - Silva, Andressa Karollini e (Universidade Federal do Tocantins, 2023)
The present report has the goal to describe the activities developed at the University Veterinary Hospital of the Universidade Federal de Santa Maria – HVU/UFSM, located in the city of Santa Maria, RS, during the Curricular Supervised Internship, which was fulfilled in the area of Medical Clinic for Small Animals in the period from 06/01/2015 to 08/28/2015. In addition to the description of these activities and the presentation of clinical cases followed during the internship period, will be discussed the topic about exocrine pancreatic insufficiency, through of a literature review, presentation of a case study and discussion. The pancreatic disease in its various forms, is not uncommon in dog and cats. The exocrine pancreatic insufficiency is a disease consequent from inadequate secretion of pancreatic enzymes, resulting in incomplete digestion of food and malabsorption of nutrients. The clinical diagnosis is difficult because it is based on history, and clinical signs; however, these are non-specific and do not distinguish other causes of malabsorption, requiring associate them to the results of laboratory tests. Usually the primary pathological process is irreversible and requires a treatment throughout his life. Some dogs may not have the resolution of all clinical signs, but they have a good quality and life expectancy.